2009
DOI: 10.1534/genetics.108.097600
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Expression Pattern of Tetracycline-Regulated Transgenes in Mice

Abstract: In generating a conditional transgenic murine model based on a tetracycline-regulated system, we obtained unexpected patterns of expression due to the transcriptional inactivity of the tet-responder promoter. Here we show strong cell-type-restricted expression that was variegated to an extent determined by the number of responder transgene copies integrated into the host genome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…However, the RT-PCR amplification of human lamin A and lamin Adel150 yielded very weak signals, even after 35 cycles of amplification (Figures 1A–1C). The weak signal was also observed in samples that did not carry the reverse transactivator transgene (Figure 1B), which suggested that the weak amplification product occurred due to the leakiness of the system, which has been reported in previous studies that used the tet-ON/OFF model systems [20][22]. A positive control reaction was performed using cDNA synthesized from RNA extracted from the bone of a previously reported animal model containing the tet-OFF system with the same lamin A target gene, available in the lab [18].…”
Section: Resultssupporting
confidence: 74%
“…However, the RT-PCR amplification of human lamin A and lamin Adel150 yielded very weak signals, even after 35 cycles of amplification (Figures 1A–1C). The weak signal was also observed in samples that did not carry the reverse transactivator transgene (Figure 1B), which suggested that the weak amplification product occurred due to the leakiness of the system, which has been reported in previous studies that used the tet-ON/OFF model systems [20][22]. A positive control reaction was performed using cDNA synthesized from RNA extracted from the bone of a previously reported animal model containing the tet-OFF system with the same lamin A target gene, available in the lab [18].…”
Section: Resultssupporting
confidence: 74%
“…Anti-SOD1 has been used previously (Raoul et al, 2005; Basso et al, 2006; Bao-Cutrona and Moral, 2009) and was validated and characterized in conjunction with the Human Protein Atlas (HPA) Project (HPA001401; http://www.proteinatlas.org). The next day, sections were washed and incubated in biotinylated secondary antibodies (1:1000; Vector Laboratories, Burlingame, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Several causes of variegated transgene expression have been proposed. Transgenes often insert as concatemers and an inverse relationship between transgene copy number and transgene silencing was reported (Bao‐Cutrona and Moral, ; Garrick et al ., ). However, repeat‐induced gene silencing was not found to be the principal reason for transgene variegation by others (Williams et al ., ) and differences in transgene copy numbers did not correlate with variegated transgene expression in the present study (Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 99%